Youth and Abuse of Substances - Khadka, Chetan (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2023)
The following comprehensive and thorough literature review focuses on Youth and Abuse of Substances. More specifically, this study describes in twenty first century youth are more into abuse of substances, the types of substances described in the currently available literature, the various existing prevention and treatment programs, factors which have been attributed to youth and abuse of substances, and focuses on areas in this field that need further research. More complaint of this study is to focuses on youth mental health and motivation towards abuse of substances. Secondary sources were utilized, providing a complete picture of the ever-growing challenge of youth and abuse of substances. This study shall then conclude with the author’s personal integration of this information, and how this information can potentially benefit professionals working with peripheral population.